EDUCATIONAL ENVIRONMENT AMONG HIGHER EDUCATIONAL INSTITUTIONS OF CULTURE AND ARTS AS AN FACTOR OF ACTUALIZATION OF DEVELOPMENT OF CREATIVE POTENTIAL OF FUTURE CHOREOGRAPHERS - Zavgorodnyaya, Evgeniya E. (Educological discourse, 2015)
An educational environment as factor of optimization of development of creative potential of future choreographers is considered in the article. The system of preparation of future specialists is considered to development of creative possibilities, that envisages internal activity of personality tangentially the specially organized process of forming of creative possibilities. Abilities, that assist pedagogical searching-converting activity the result of that are further professional development and саморазвитие, are analysed.